Macroeconomic determinants of Malaysian housing price: evidence from 2010Q1 - 2017Q3 - Chong, Jing Wen; Koo, Chien Hui; Lim, Jia Ler; Wong, Joo Chin; Wong, Poh Wen (2019)
The main purpose of this study is to measure the significant relationship between macroeconomic factors and movements of housing price in Malaysia from period year 2010 Quarter 1 to year 2017 Quarter 3, which consist of quarterly data of 31 observations. The continuous increase of housing price in Malaysia is becoming one of the hot issues discussed these days. This paper examines empirically whether the increasing trend of housing price in Malaysia is related to changes in Gross Domestic Product (GDP), Exchange Rate (ER), Lending Rate (LR), and Unemployment Rate (UR). Ordinary Least Square (OLS) method is applied in this study, with the purpose of capturing the effect of independent variables. The data of the variables in this study are obtained through the secondary sources. This paper is useful for the government, developers, investors and home buyers to know which factors is most affected the movement of property price investment decision. Thus, this paper can serve as a guide for the government in stabilizing the residential property price in Malaysia. The general results of the study obtained found that Exchange Rate (ER), Lending Rate (LR), and Real Property Gain Tax (RPGT) have the significant relationship in determining the Malaysian housing price index (MHPI), whereas the Gross Domestic Product (GDP) and Unemployment Rate (UR) have the insignificant relationship in determining the housing price index of Malaysia.